Post-progression outcomes following BCMA-directed CAR T-cell therapy in myeloma: impact of extramedullary and paramedullary disease - Abuhelwa, Ziad; Amisha, Fnu; Fan, Wenyi; De Avila, Gabriel; Hansen, Doris K.; Grajales-Cruz, Ariel F.; Blue, Brandon; Castaneda, Omar; Liu, Hien; Freeman, Ciara L.; Nishihori, Taiga; Locke, Frederick L.; et al. (Frontiers in Oncology, 2025)
IntroductionBCMA-directed CAR T-cell therapies have improved outcomes in relapsed and refractory multiple myeloma (MM); however, the majority of patients relapse within 1 to 3 years following treatment. Managing disease progression after CAR T-cell therapy remains a major challenge, particularly in aggressive subtypes including extramedullary disease (EMD) and paramedullary disease (PMD). Real-world data on progression patterns post-CAR T cell therapy and the impact of EMD or PMD on outcomes of patients who relapsed post-CAR T-cell therapy remain scarce.MethodsIn this single-center, retrospective study, we evaluated progression patterns and survival outcomes in 106 MM patients who progressed after commercial CAR T-cell therapy (ide-cel or cilta-cel) between May 2021 and December 2023. Overall survival (OS) was defined from the time of post-CAR T-cell therapy progression to death or last follow-up, and progression-free survival (PFS) from post-CAR T-cell therapy progression to progression on the next line of therapy.ResultsBiochemical relapse occurred in 82% of patients, with EMD or PMD present in 51% at progression. Baseline EMD at the time of CAR T-cell infusion was detected in 33% of patients and was associated with significantly inferior PFS (3.6 vs. 7.0 months, p=0.0076) and OS (4.8 vs. 21.0 months, p=0.00086) compared to those without EMD. Similarly, the presence of EMD at progression was associated with shorter PFS (4.7 vs. 8.5 months, p=0.022) and OS (7.4 vs. 21.1 months, p=0.035). Patients who were EMD positive at both baseline and progression had the poorest outcomes. PMD at baseline or progression was not significantly associated with worse survival.DiscussionOur findings highlight that post-CAR T-cell progression in MM is heterogeneous and that EMD confers an adverse prognosis, emphasizing the critical need for imaging surveillance. Strategies such as bridging therapies aimed at reducing tumor burden prior to CAR T-cell infusion or maintenance therapies post-CAR T-cell therapy warrant further investigation to optimize responses and improve long-term survival in this high-risk population.